Cladocera (Crustacea: Branchiopoda) of the south-east of the Korean Peninsula, with twenty new records for Korea - Kotov, Alexey A.; Jeong, Hyun Gi; Lee, Wonchoel (Zootaxa, 2012)
We studied the cladocerans from 15 different freshwater bodies in south-east of the Korean Peninsula. Twenty species are first records for Korea, viz. 1. Sida ortiva Korovchinsky, 1979; 2. Pseudosida cf. szalayi (Daday, 1898); 3. Scapholeberis kingi Sars, 1888; 4. Simocephalus congener (Koch, 1841); 5. Moinodaphnia macleayi (King, 1853); 6. Ilyocryptus cuneatus Štifter, 1988; 7. Ilyocryptus cf. raridentatus Smirnov, 1989; 8. Ilyocryptus spinifer Herrick, 1882; 9. Macrothrix pennigera Shen, Sung & Chen, 1961; 10. Macrothrix triserialis Brady, 1886; 11. Bosmina (Sinobosmina) fatalis Burckhardt, 1924; 12. Chydorus irinae Smirnov & Sheveleva, 2010; 13. Disparalona ikarus Kotov & Sinev, 2011; 14. Ephemeroporus cf. barroisi (Richard, 1894); 15. Camptocercus uncinatus Smirnov, 1971; 16. Camptocercus vietnamensis Than, 1980; 17. Kurzia (Rostrokurzia) longirostris (Daday, 1898); 18. Leydigia (Neoleydigia) acanthocercoides (Fischer, 1854); 19. Monospilus daedalus Kotov & Sinev, 2011; 20. Nedorchynchotalona chiangi Kotov & Sinev, 2011. Most of them are illustrated and briefly redescribed from newly collected material. We also provide illustrations of four taxa previously recorded from Korea: Sida crystallina (O.F. Müller, 1776); Macrothrix rosea (Jurine, 1820); Bosmina (Bosmina) longirostris (O. F. Müller, 1776) and Disparalona cf. hamata (Birge, 1879). Among the newly recorded taxa, there are six Far East endemics; five tropicopolitan species for which the Amur basin is the northernmost margin of their distribution; four tropicopolitan species for which Korea is presumed to be the northern most area of their distribution; two Palaearctic taxa for which Korea could be the southern most area of their distribution; two cosmopolitan species which need to be revised; and one species widely distributed in Eastern Asia. Despite significantly increasing the number of known species of cladocerans in Korea, we recognize that further research is needed to complete the picture, and the cosmopolitan taxa need further revision.